# 009A Sample Midterm 2, Problem 1 Detailed Solution

Evaluate the following limits.

(a) Find  $\lim _{x\rightarrow 2}{\frac {{\sqrt {x^{2}+12}}-4}{x-2}}$ (b) Find  $\lim _{x\rightarrow 0}{\frac {\sin(3x)}{\sin(7x)}}$ (c) Evaluate  $\lim _{x\rightarrow ({\frac {\pi }{2}})^{-}}\tan(x)$ Background Information:
Recall
$\lim _{x\rightarrow 0}{\frac {\sin x}{x}}=1$ Solution:

(a)

Step 1:
We begin by noticing that if we plug in  $x=2$ into
${\frac {{\sqrt {x^{2}+12}}-4}{x-2}},$ we get   ${\frac {0}{0}}.$ Step 2:
Now, we multiply the numerator and denominator by the conjugate of the numerator.
Hence, we have
${\begin{array}{rcl}\displaystyle {\lim _{x\rightarrow 2}{\frac {{\sqrt {x^{2}+12}}-4}{x-2}}}&=&\displaystyle {\lim _{x\rightarrow 2}{\frac {({\sqrt {x^{2}+12}}-4)}{(x-2)}}{\frac {({\sqrt {x^{2}+12}}+4)}{({\sqrt {x^{2}+12}}+4)}}}\\&&\\&=&\displaystyle {\lim _{x\rightarrow 2}{\frac {(x^{2}+12)-16}{(x-2)({\sqrt {x^{2}+12}}+4)}}}\\&&\\&=&\displaystyle {\lim _{x\rightarrow 2}{\frac {x^{2}-4}{(x-2)({\sqrt {x^{2}+12}}+4)}}}\\&&\\&=&\displaystyle {\lim _{x\rightarrow 2}{\frac {(x-2)(x+2)}{(x-2)({\sqrt {x^{2}+12}}+4)}}}\\&&\\&=&\displaystyle {\lim _{x\rightarrow 2}{\frac {x+2}{{\sqrt {x^{2}+12}}+4}}}\\&&\\&=&\displaystyle {\frac {4}{8}}\\&&\\&=&\displaystyle {{\frac {1}{2}}.}\end{array}}$ (b)

Step 1:
First, we write
${\begin{array}{rcl}\displaystyle {\lim _{x\rightarrow 0}{\frac {\sin(3x)}{\sin(7x)}}}&=&\displaystyle {\lim _{x\rightarrow 0}{\frac {\sin(3x)}{x}}{\frac {x}{\sin(7x)}}}\\&&\\&=&\displaystyle {\lim _{x\rightarrow 0}{\frac {3}{7}}{\frac {\sin(3x)}{3x}}{\frac {7x}{\sin(7x)}}}\\&&\\&=&\displaystyle {{\frac {3}{7}}\lim _{x\rightarrow 0}{\frac {\sin(3x)}{3x}}{\frac {7x}{\sin(7x)}}.}\end{array}}$ Step 2:
Now, we have

${\begin{array}{rcl}\displaystyle {\lim _{x\rightarrow 0}{\frac {\sin(3x)}{\sin(7x)}}}&=&\displaystyle {{\frac {3}{7}}\lim _{x\rightarrow 0}{\frac {\sin(3x)}{3x}}{\frac {7x}{\sin(7x)}}}\\&&\\&=&\displaystyle {{\frac {3}{7}}{\bigg (}\lim _{x\rightarrow 0}{\frac {\sin(3x)}{3x}}{\bigg )}{\bigg (}\lim _{x\rightarrow 0}{\frac {7x}{\sin(7x)}}{\bigg )}}\\&&\\&=&\displaystyle {{\frac {3}{7}}(1)(1)}\\&&\\&=&\displaystyle {{\frac {3}{7}}.}\end{array}}$ (c)

Step 1:
First, we write
$\lim _{x\rightarrow {\big (}{\frac {\pi }{2}}{\big )}^{-}}\tan x=\lim _{x\rightarrow {\big (}{\frac {\pi }{2}}{\big )}^{-}}{\frac {\sin x}{\cos x}}.$ Step 2:
When we plug in values a little smaller than  ${\frac {\pi }{2}}$ into   ${\frac {\sin x}{\cos x}},$ we get a small denominator, which results in a large number.
Thus,
$\lim _{x\rightarrow {\big (}{\frac {\pi }{2}}{\big )}^{-}}{\frac {\sin x}{\cos x}}$ is either equal to  $\infty$ or  $-\infty .$ Step 3:
Since we are calculating a left hand limit, we are considering angles in the first quadrant.
In the first quadrant,  $\sin x$ and  $\cos x$ are both positive.
Hence,
$\lim _{x\rightarrow {\big (}{\frac {\pi }{2}}{\big )}^{-}}{\frac {\sin x}{\cos x}}=\infty .$ (a)     ${\frac {1}{2}}$ (b)     ${\frac {3}{7}}$ (c)     $\infty$ 